Design of automated testing stand for development and optimizing precision liquid dispensing algorithms on weighing scale - Kurdiumov, D. S. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The research is dedicated to the development of an automated testing stand for refining liquid dispensing algorithms on weighing scales in industrial processes. The use of computer modeling enables efficient experiments without physical creation of prototypes, thus enhancing the quality and efficiency of industrial production. The expected outcomes of the research include the development of equipment design methods and successful implementation into industrial practice, opening new perspectives for enhancing the quality of industrial processes.
Keywords: automated liquid dispensing; testing stands; automated testing; dosing algorithms; computer modeling; industrial processes